Interest rate policy and exchange rates volatility lessons from Indonesia - Haryo Kuncoro (Journal of Central Banking Theory and Practice, 2020)
Whether or not inflation targeting adoption leads to increased volatility of exchange rates is controversial. The volatility increases with inflation targeting as a result of the flexible exchange rate regime. Others argue that inflation targeting delivers the best outcomes in terms of lower exchange rate volatility. The purpose of this paper is to investigate whether interest rate policy in inflation targeting frameworks - that is subjected to control inflation rate - may reduce the volatility of exchange rates. To test the hypothesis, we use monthly data in the case of Indonesia over the period 2005(7)-2016(7). Several control variables are introduced in the regressions. The result of the autoregressive distributed lag model proves the interest rate policy and foreign exchange intervention fail to reduce the exchange rates volatility. It seems inflation targeting in Indonesia puts too much emphasis on stabilizing the domestic currency thus leading to benign neglect of stabilizing its external value, ultimately resulting in increased exchange rate volatility. These findings suggest that central bank credibility plays an important role in conducting inflation targeting policy which operates primarily through a signalling effect.
Keywords: E42; E52; E58; F31; 330; Inflation Targeting; Interest Rate Policy; International Reserve; Exchange Rates Volatility; ARDL